Development of release velocity and spin prediction models for passing machines in American football - Hollaus, B.; Raschner, C.; Mehrle, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
This article focuses on the development of release velocity and spin prediction models for oval shaped footballs with a state-of-the-art passing machine. Since the trajectory of the ball can be predicted with aerodynamic models, the state of the ball at release time is of interest. At present, no prediction model for this initial state exists. This study measured release spin and velocity. A prediction model was developed based on various ball wear and measured release spin and velocity for different machine configurations. To sensor the motion, a high-speed camera with post image processing was used and release spin and velocity were calculated via regressions. The goal was to predict the release velocity within ±3% in 90% of all relevant cases, depending on the passing machine`s configuration. In addition, the dependency on the wear of the football was investigated. The results show that the release velocity can be predicted, independently of the wear of the ball, with the required accuracy for a reasonable range of machine configurations. For the release spin, a less accurate prediction model was developed. Both prediction models, their limitations and determination are presented in graphical form.